EFFECT OF DIFFERENT SUBSTRATES ON BIOFILM GROWTH AND LIPID CONTENT OF DIATOM Thalassiosira sp. - Tabaquirao, Joan Torrento; Dionela, Cleresa Salido; Huervana, Fredson Hervias; Traifalgar, Rex Ferdinand Mallare (Indonesian Aquaculture Journal, 2025)
Diatoms are valuable as natural feed in aquaculture due to their lipid content and the presence of essential polyunsaturated fatty acids (PUFAs), including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). While traditional suspended cultivation has limitations, attached cultivation offers advantages such as lower water use and improved lipid productivity. This study evaluated the growth, biomass, and lipid content of Thalassiosira sp. grown on polycarbonate (PC) and polyvinyl chloride (PVC) as attachment substrates. The control group was cultured in standard suspended cultivation method.  Test attachments substrates were submerged in sterile seawater enriched with F-medium, and growth was monitored for four days.  At day 4 of the culture, cell density was significantly higher on PC (13.08 × 105 cells mL-1) and PVC (13.01 × 105 cells mL-1) compared to the control (7.93 × 105 cells mL-1). The specific growth rate was also significantly higher on both substrates, exhibiting a doubling time of 0.20 days. Biomass accumulation was highest on PC (27.47 mg 100 mL-1), followed by PVC (26.87 mg 100 mL-1), representing increases of 38.39% and 35.37% over the control (19.85 mg 100 mL-1), respectively. Lipid content was higher in the attached culture system, reaching 8.50% on PC and 7.45% on PVC, corresponding to increases of 167.30% and 134.28% over the control (3.18%). These findings highlight the potential of PC and PVC as effective substrates for biofilm-based cultivation of Thalassiosira sp., demonstrating superior growth, biomass yield, and lipid accumulation compared to the suspended culture method.